2019
DOI: 10.2174/1874944501912010001
|View full text |Cite
|
Sign up to set email alerts
|

Distal Forearm Bone Mineral Density Among Hill Tribes in the Omkoi District, Chiang Mai Province, Thailand

Abstract: Background: Osteoporosis is a major public health issue in several countries worldwide because it increases healthcare costs, and is a risk for mortality. There have been several studies that have examined BMD among the various Thai people and the regions that they inhabit. Objective: This study examined the distal forearm Bone Mineral Density (BMD) in men and women over 40 years of age among members of various Karen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…Our data was compared to previously reports. 18 The current study found incremental decreases in the distal forearm BMD and incrementally decreases took place in the T-scores when age-group increased. The current results were similar to the studies that were conducted by Thumvijit et al The female BMD distal forearm plotted against age, BMI, height, and weight are shown in Figure 2.…”
Section: Resultssupporting
confidence: 54%
See 4 more Smart Citations
“…Our data was compared to previously reports. 18 The current study found incremental decreases in the distal forearm BMD and incrementally decreases took place in the T-scores when age-group increased. The current results were similar to the studies that were conducted by Thumvijit et al The female BMD distal forearm plotted against age, BMI, height, and weight are shown in Figure 2.…”
Section: Resultssupporting
confidence: 54%
“…We also compared the data from Doi Lo District with data obtained from Mae Chaem and Omkoi Districts which are located in the same province of Chiang Mai, Thailand. For the female group, T-scores from Doi Lo district population at 40-49 (years) was similar to Mae Chaem 19 and Omkoi Districts 18 whereas T-scores from Doi Lo District population at 50-59 years and 60-69 years were higher than Mae Chaem 19 and Omkoi Districts. 18 For the male group, T-scores from the Doi Lo District population was less than in Mae Chaem 19 but were higher than the Omkoi District for all agegroups.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations